Cruzain Inhibitors: State-of-Art of Novel Synthetic Strategies - Bezerra Morais, Pedro A.; Goulart Trossini, Gustavo Henrique (Current Organic Chemistry, 2023)
Concerned about a million people are infected worldwide, and other millions are living at risk zones of infection. Chagas disease causes 10 000 deaths annually, and the discovery of safe and effective drugs on a nanomolar scale has been headlined as a crucial goal by the worldwide research community and international health agencies. Nifurtimox and Benznidazole are the only marketed drugs for Chagas disease therapy, with the mode of action depending on the formation of free radicals. Thus, diverse studies have revealed cysteine proteases from T. cruzi as well-established targets for drug discovery. Validation of cruzain as a promising target has been based on several findings on the molecular biology of T. cruzi. Hence, several inhibitor classes have been elucidated, consisting of peptidic and nonpeptidic, and covalent and noncovalent. Thus, we present a perspective for the synthesis of novel cruzain inhibitors from scaffolds both recently approached and well established with an IC50 range of micromolar to nanomolar and supported by computational techniques.
Keywords: medicinal